2022
DOI: 10.3389/fviro.2022.833106
|View full text |Cite
|
Sign up to set email alerts
|

Host-Viral Interactions at the Maternal-Fetal Interface. What We Know and What We Need to Know

Abstract: In humans, the hemochorial placenta is a unique temporary organ that forms during pregnancy to support fetal development, gaseous exchange, delivery of nutrition, removal of waste products, and provides immune protection, while maintaining tolerance to the HLA-haploidentical fetus. In this review, we characterize decidual and placental immunity during maternal viral (co)-infection with HIV-1, human cytomegalovirus (HCMV), and Zika virus. We discuss placental immunology, clinical presentation, and epidemiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…However, we also identified a more nuanced relationship between ART duration and fetal growth, whereby ART started in the second half of pregnancy (< 20 weeks duration) and ART started preconception (> 40 weeks duration) were both associated with increased LBW and VLBW compared to ART started during the first half of pregnancy (20-< 40 weeks duration). For pregnancies where ART is only started later, the fetus is exposed to a perturbed in utero environment for substantially longer, compared to ART started early in pregnancy in which the maternal immune system has potentially stabilized by the time fetal weight gain is expected to accelerate later in pregnancy [ 30 ]. ART duration >40 weeks, that is mostly preconception, was not as detrimental as late pregnancy ART initiation (<20 weeks duration) but was still significantly associated with LBW and VLBW compared to early pregnancy ART initiation (20-<40 weeks duration), likely after the time of conception.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also identified a more nuanced relationship between ART duration and fetal growth, whereby ART started in the second half of pregnancy (< 20 weeks duration) and ART started preconception (> 40 weeks duration) were both associated with increased LBW and VLBW compared to ART started during the first half of pregnancy (20-< 40 weeks duration). For pregnancies where ART is only started later, the fetus is exposed to a perturbed in utero environment for substantially longer, compared to ART started early in pregnancy in which the maternal immune system has potentially stabilized by the time fetal weight gain is expected to accelerate later in pregnancy [ 30 ]. ART duration >40 weeks, that is mostly preconception, was not as detrimental as late pregnancy ART initiation (<20 weeks duration) but was still significantly associated with LBW and VLBW compared to early pregnancy ART initiation (20-<40 weeks duration), likely after the time of conception.…”
Section: Discussionmentioning
confidence: 99%
“…MDMX is predominantly expressed (Fig. 3C and D) on Hofbauer cells (HC) [36][37][38][39][40] that are targets of Zika and other viruses [41]. Strong MDMX staining was limited to the cytoplasm of HC, easily identified within the villous stroma, some within stromal channels (Fig.…”
Section: Immunohistochemistry and Whole Mount Immunofluorescencementioning
confidence: 99%
“…Since more recent studies have shown that purified Kupffer cells are highly permissive to HIV-1 infection in vitro, some authors propose that these resident macrophages could play important role in driving hepatic inflammation and fibrosis in infected patients (for review, see [ 42 ]). Similarly, HIV-1 infection of the placental Hofbauer macrophages was recognized early as they are central mediators of vertical mother-to-child HIV-1 transmission during pregnancy (for reviews, see [ 43 , 44 , 45 , 46 ]). Furthermore, it was recently reported that Hofbauer cells isolated from early- and mid-gestation are rather resistant to HIV-1 replication in vitro, compared to the higher susceptibility of term-gestation Hofbauer cells [ 47 ].…”
Section: Macrophages As Cellular Targets Of Hiv-1 In Vivomentioning
confidence: 99%